PENERAPAN RETRIEVAL-AUGMENTED GENERATION(RAG) DAN LARGE LANGUAGE MODEL(LLM) PADA CHATBOT PELAYANAN PUBLIK DINAS ADMINISTRASI DAN DAN PENCATATAN SIPIL KABUPATEN MUSI RAWAS UATARA - Ari Bauceng; Adri Anto Tri Susilo; Harma Oktavia Lingga Wijaya; Asep Toyib Hidayat (Jurnal Teknologi Informasi Mura (JTI), 2026)
The development of information technology encourages government agencies to improve the quality of public services through digital services. The Population and Civil Registration Office (Disdukcapil) of North Musi Rawas Regency is required to provide fast and easily accessible population administration services. This study designed and implemented a WhatsApp-based chatbot as a population information service medium. The methods used included needs analysis, system design, implementation, and functionality testing. The chatbot provides information related to document requirements, service schedules, administrative flows, and officer contact features. The implementation results show that the system is able to improve service efficiency, facilitate information access, and reduce the burden of manual service. This chatbot has the potential to become an adaptive and sustainable digital public service solution.